2013
DOI: 10.1186/1749-799x-8-49
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic morphogenetic protein vs. recombinant human bone morphogenetic protein-2 in lumbar interbody fusion procedures: a radiographic and economic analysis

Abstract: BackgroundSince the introduction of rhBMP-2 (Infuse®) in 2002, surgeons have had an alternative substitute to autograft and its related donor site morbidity. Recently, the prevalence of reported adverse events and complications related to the use of rhBMP-2 has raised many ethical and legal concerns for surgeons. Additionally, the cost and decreasing reimbursement landscape of rhBMP-2 use have required identification of a viable alternative. Osteo allogeneic morphogenetic protein (OsteoAMP®) is a commercially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…Data from the current study demonstrated over 98% fusion rates for both lumbar and cervical patients at 18 months. This confirms the results from previous studies using OsteoAMP where reported fusion results of 98.9% at 18 months in lumbar and 100% at 18 months in cervical cases when OsteoAMP was used as the biologic [22,23]. We found no biological adverse events, although one patient did develop a pseudarthrosis without a clear reason.…”
Section: Discussionsupporting
confidence: 91%
“…Data from the current study demonstrated over 98% fusion rates for both lumbar and cervical patients at 18 months. This confirms the results from previous studies using OsteoAMP where reported fusion results of 98.9% at 18 months in lumbar and 100% at 18 months in cervical cases when OsteoAMP was used as the biologic [22,23]. We found no biological adverse events, although one patient did develop a pseudarthrosis without a clear reason.…”
Section: Discussionsupporting
confidence: 91%
“…It is being evaluated in transforaminal and lateral lumbar interbody fusion procedures as an alternative to rhBMP-2. In a clinical study, 226 patients received OsteoAMP with autologous local bone, while 95 patients received Infuse with autologous local bone [93]. The fusion rates were systematically higher and the time required to achieve fusion was approximately 40% less than rhBMP-2 with about 70% fewer complications.…”
Section: Bone Graft Substitutes Combined With Active Biomoleculesmentioning
confidence: 99%
“…This is the case of OsteoAMP ® (Bioventus Surgical) and Augment ® bone graft (Wright Medical Group), the former made of an allogeneic-derived matrix, especially treated to preserve a cocktail of native growth factors and the latter composed of a collagen/tricalcium phosphate composite combined with platelet-derived growth factor (PDGF-BB). Both devices promoted bone ingrowth without the need of autograft harvesting in two clinical trials with patients undergoing transforaminal lumbar or lateral interbody fusion and ankle or hindfoot arthrodesis, respectively ( DiGiovanni et al, 2013 ; Roh et al, 2013 ; Krell and DiGiovanni, 2016 ).…”
Section: Enhancing Bone Regeneration With Bioactive Materialsmentioning
confidence: 99%